Build a World Wide Web commerce center : plan, program, and manage Internet commerce for your company - Net.Genesis; Net.Genesis (Firm) (New York : Wiley, 1996)
From net. Genesis Corporation, cutting-edge pioneers in Web site software development, comes this comprehensive guide to creating a state-of-the-art commerce center on the World Wide Web. This book teaches Webmasters and businesses of all sizes how to use Windows NT-based Web server software to establish a secure and sophisticated commerce site. The savvy techniques and guidelines in this book open up the exploding Web marketplace to a broad new range of businesses, small and large, by making electronic commerce manageable and affordable. Build a World Wide Web Commerce Center integrates all of the crucial technical and business issues you'll need to master to set up a secure Windows NT Web commerce server, prepare content for the site, and support marketing and selling functions
Ch. 1. Getting Down to Business on the World Wide Web -- Ch. 2. Why You Can Build Your Own Commerce Server Now -- Ch. 3. Beyond Publishing and on to Commerce -- Ch. 4. The Business Side of a Web Site -- Ch. 5. Web Server Technology Primer -- Ch. 6. Under the Hood of Your Web Server PC -- Ch. 7. Setting Up NT as Your Web Serving Platform -- Ch. 8. Getting Wired to the Net -- Ch. 9. Web Server Software Primer -- Ch. 10. Test Driving Microsoft's Internet Information Server -- Ch. 11. Test Driving Netscape's Commerce Server -- Ch. 12. Test Driving O'Reilly's WebSite Professional -- Ch. 13. Essential Web Commerce Server Tools -- Ch. 14. Tracking Your Web Site Activity -- Ch. 15. Creating Forms and Integrating Databases -- Ch. 16. Customer Support Using Discussion Groups -- Ch. 17. Bells, Whistles, and Future Directions -- Appendix: Webmaster Resources
Keywords: Microsoft Windows NT; Business enterprises -- Computer networks; Electronic commerce; Web servers; Web sites